Experiences of Gender-Based Stigma in Health Care in North America: A Mixed-Methods Scoping Review and Synthesis of the Literature - Stephanie A. Meyers-Pantele; Junye Ma; Keith J. Horvath; Ingrid Yu; Carmen H. Logie; Claudia Rafful; Valerie A. Earnshaw (Women's Health Reports)
Background: Gender-based stigma (GBS) is widely recognized as a barrier to health care-related outcomes globally, including in North America. Although GBS permeates health care institutions, little research has examined the individual-level experiences of GBS in health care, how these may intersect with other marginalized social positions, or how GBS shapes health care outcomes. Materials and Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines, this scoping review synthesized the peer-reviewed English scientific literature, through April 2023, on GBS related to health care for cisgender persons. Articles were included if they were from North America and quantitatively or qualitatively investigated either (1) experiences of GBS in health care settings or (2) the relationship between GBS and health care outcomes (e.g., health care access, health care engagement, and treatment adherence). Results: Of the 25 studies included, the quantitative articles (n = 13) demonstrated mixed findings regarding both the prevalence of experiences of GBS in health care (8 − 53%) and the impact of GBS on health care outcomes. However, all (n = 14) of the qualitative articles demonstrated that GBS negatively shapes health care experiences, particularly for those occupying intersectional social positions, and is influenced by societal gender norms. Furthermore, gendered experiences of violence and abuse negatively shape care outcomes, both inside and outside of health care contexts. Conclusions: The quantitative literature lacks consensus regarding the influence of GBS in health care, but the qualitative literature more clearly demonstrates GBS’s deleterious effect on health care, especially for women. The use of validated GBS measures and intersectional approaches is needed to fully understand the role of GBS in health care.